2019
DOI: 10.1177/2040206619889220
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Ebola virus VP35 homo-dimerization on the type I interferon cascade inhibition

Abstract: Ebola virus high lethality relies on its ability to efficiently bypass the host innate antiviral response, which senses the viral dsRNA through the RIG-I receptor and induces type I interferon a/b production. In the bypassing action, the Ebola virus protein VP35 plays a pivotal role at multiple levels of the RIG-I cascade, masking the viral 5 0-triphosphorylated dsRNA from RIG-I, and interacting with other cascade components. The VP35 type I interferon inhibition is exerted by the C-terminal domain, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 62 publications
(100 reference statements)
0
9
1
Order By: Relevance
“…Since EBOV inhibition of the IFN response massively contributes to viral pathogenesis (4, 5), restoring the IFN system could represent a promising strategy for EBOV control (13). Two viral proteins have been demonstrated to suppress interferon responses, VP35 and VP24 (13,39). Different studies have shown that it is possible to block VP35 IFN-inhibitory function with natural compounds (11,12) and also antibodies ( 14), thus restoring the IFN production cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Since EBOV inhibition of the IFN response massively contributes to viral pathogenesis (4, 5), restoring the IFN system could represent a promising strategy for EBOV control (13). Two viral proteins have been demonstrated to suppress interferon responses, VP35 and VP24 (13,39). Different studies have shown that it is possible to block VP35 IFN-inhibitory function with natural compounds (11,12) and also antibodies ( 14), thus restoring the IFN production cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al also found that the N-terminal hydrophobic TMS, but not the C-terminal hydrophilic region of M, was important for the response, confirming the results of Siu et al [ 312 ]. The M-mediated interferon antagonism noted here seems to be a common characteristic of a large number of (but definitely not all) viruses from different viral classifications [ 314 , 315 ].…”
Section: Viral Responses To and Interference With Normal Cellularmentioning
confidence: 99%
“…Many viruses also encode proteins that help conceal their genetic material from PRR. Some viruses possess dsRNA binding proteins that could potentially sequester these PAMPs from PPR recognition, such as VP35 from Ebola virus or σ3 from reovirus [ 73 , 74 ]. The encapsidation of the viral RNA can also impair RLR recognition.…”
Section: Viral Evasion Strategies: Inhibition Of Interferon Inductionmentioning
confidence: 99%